Desain Instruksional Project Based Learning Berbasis Steam Bermuatan Sustainability pada Materi Pencemaran Air untuk Siswa SMK - Sonia Fitria; Eny Hartadiyanti WH (Universitas Sebelas Maret, 2025)
The 21st century learning, including in SMK (vocational high schools), requires a STEAM-based (Science, Technology, Engineering, Arts, and Mathematics) learning approach. The STEAM approach is selected because it integrates various interrelated disciplines to develop 21st-century competencies and fosters awareness of environmental issues in a sustainable context. This study aims to design a STEAM-based instructional model that incorporates sustainability aspects using the PJBL (Project-Based Learning) model on the topic of water pollution for Vocational High School students. The research method used is descriptive qualitative, with data collected through literature review and interviews. The result of this study is an instructional design using the PjBL model with sustainability-embedded STEAM-based syntax: (1) formulating essential questions integrated with the Science element, focusing on water pollution and its solutions; (2) designing a project directed toward the Technology element, specifically ecoprint as an environmentally friendly alternative (reflecting sustainability), applied to fashion product engineering (Engineering element), expressing aesthetic value through ecoprint products (Art element), and calculating raw material needs, capital efficiency, and production costs of ecoprint (Mathematics element); (3) scheduling project implementation over three weeks; (4) monitoring the process from design to product outcome; and (5) evaluating project results through an exhibition.